Enhancement of oral bioavailability of quercetin by metabolic inhibitory nanosuspensions compared to conventional nanosuspensions. (1st January 2021) - Li, Haowen; Li, Manzhen; Fu, Jingxin; Ao, Hui; Wang, Weihua; Wang, Xiangtao
Abstract: Quercetin-loaded nanosuspensions (Que-NSps) added metabolic inhibitors were evaluated as drug delivery system to promote the oral bioavailability of quercetin. Que-NSps were prepared respectively using d -alpha tocopherol acid polyethylene glycol succinate (TPGS) or Soybean Lecithin (SPC) as stabilizer. On the basis, Piperine (Pip) or sodium oleate (SO) was, respectively, encapsulated in Que-NSps as phase II metabolic inhibitors. The resulting Que-NSps all displayed a mean particle size of about 200 nm and drug loading content was in the range of 22.3–27.8%. The release of quercetin from Que-NSps was slow and sustained. After oral administration of 50 mg/kg different Que-NSps, the levels of free quercetin in plasma were significantly promoted, the concentration of quercetin metabolites (isorhamnetin and quercetin 3-O-β-d -Glucuronide) were decreased. The absolute bioavailability was, respectively 15.55%, 6.93%, 12.38%, and 23.58% for TPGS-Que-NSps, TPGS-SO-Que-NSps, SPC-Que-NSps, and SPC-Pip-Que-NSps, and 3.61% for quercetin water suspension. SPC-Pip-Que-NSps turned out to an ideal nanocarrier combined nano drug delivery system together with metabolic inhibitor to promote oral absorption of quercetin.